(untitled) (Innovative professional education, 2024)
Environmental concept in the context of the structure of the readiness of social pedagogues to work with veterans of military service were studied. The impact of healthy environment and implementation of its environmental protection on the aspects of readiness (motivational, cognitive, operational and evaluative-reflective) is highlighted. The impact of the environment on the health and psychological state of veterans was analyzed, the connection between environmental changes and the need to implement appropriate pedagogical methods on the structure of the aforementioned readiness was revealed. The foundation has been laid for the integration of environmental awareness and competence into the professional activity of social educators for their work with veterans of military service.